Absorbent articles

The absorbent article incorporates a polymer absorber with a continuous skeleton and voids, achieving a balance between thinness and rapid absorption, thereby overcoming the bulkiness and slow absorption issues of conventional SAP-pulp fiber combinations.

JP7657890B2Active Publication Date: 2025-04-07UNI CHARM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023191659
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-11-09
Publication Date
2025-04-07
Estimated Expiration
2039-12-27

AI Technical Summary

Technical Problem

Conventional absorbent articles using high-absorbent polymers (SAP) combined with pulp fibers face challenges in achieving a thin profile while maintaining rapid absorption speed.

Method used

The development of an absorbent article featuring a polymer absorber with a continuous skeleton and continuous voids, accompanied by a skin-side sheet member, which achieves an absorption amount between 7.8 ml/g and 21.3 ml/g after 30 seconds in the pressureless DW method.

Benefits of technology

This solution enables the creation of an absorbent article with appropriate absorption speed and a thin absorber, addressing the bulkiness issue associated with pulp fibers while maintaining or exceeding their absorption speed performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657890000001
    Figure 0007657890000001
  • Figure 0007657890000002
    Figure 0007657890000002
  • Figure 0007657890000003
    Figure 0007657890000003
Patent Text Reader

Abstract

To provide an absorbent article (1) including a thinned absorber having proper absorption rate performance.SOLUTION: An absorbent article (1) includes a polymer absorber having continuous skeletons and continuous pores, and a skin-side sheet member provided closer to the skin side than the polymer absorber, where a liquid adsorption of the polymer absorber after 30 seconds according to a pressureless DW method is 7.8 ml / g or more and 21.3 ml / g or less.SELECTED DRAWING: Figure 10
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an absorbent article. [Background technology]

[0002] Conventionally, absorbent articles such as disposable diapers and sanitary napkins that use superabsorbent polymers (so-called "SAP") with high absorption capacity have been known. For example, Patent Document 1 discloses an absorbent article that uses an absorbent body that combines SAP with high absorption capacity and pulp fibers with high absorption speed. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2013-018571 Summary of the Invention [Problem to be solved by the invention]

[0004] It is desirable to reduce the thickness of absorbent articles from the viewpoints of distribution, storage, portability, wearing comfort, etc. However, when SAP is combined with pulp fibers, there is an issue that the absorbent body becomes bulky (the absorbent body cannot be made thin) due to the large amount of pulp in the pulp fibers.

[0005] On the other hand, if pulp fibers are eliminated and only SAP is used, the excellent absorption speed performance of pulp fibers is not exhibited, resulting in an absorbent with a slow absorption speed.

[0006] Therefore, there is a demand for an absorbent article that is thinner than an absorbent article using pulp fibers and has an absorption rate performance equal to or higher than that of an absorbent article using pulp fibers.

[0007] The present invention has been made in consideration of the above-mentioned problems, and an object of the present invention is to realize an absorbent article having a thin absorbent body with appropriate absorption rate performance. [Means for solving the problem]

[0008] The main invention to achieve the above object is: An absorbent article comprising a polymer absorbent having a continuous skeleton and continuous pores, and a skin-side sheet member provided on the skin side of the polymer absorbent, The absorbent article is characterized in that the polymer absorbent has a liquid absorption amount after 30 seconds in a non-pressure DW method of 7.8 ml / g or more and 21.3 ml / g or less.

[0009] Other features of the present invention will become apparent from the following detailed description of the present invention and the accompanying drawings. Effect of the Invention

[0010] According to the present invention, it is possible to realize an absorbent article having a thin absorbent body with appropriate absorption rate performance. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic perspective view of a pants-type disposable diaper 1. As shown in FIG. [Diagram 2] Fig. 2A is a schematic plan view of the diaper 1 in an unfolded and stretched state, as viewed from the skin side, and Fig. 2B is a schematic cross-sectional view taken along the line XX in Fig. 2A. [Diagram 3] FIG. 3 is a diagram illustrating the manufacturing process of the absorbent A. [Figure 4] FIG. 4 is an SEM photograph of absorbent A at a magnification of 50 times. [Diagram 5] FIG. 5 is a SEM photograph of absorbent A at a magnification of 100 times. [Figure 6] FIG. 6 is an SEM photograph of absorbent A at a magnification of 500 times. [Figure 7] FIG. 7 is a SEM photograph of absorbent A at a magnification of 1000 times. [Figure 8] FIG. 8 is an SEM photograph of absorbent A at a magnification of 1500 times. [Figure 9]FIG. 9 is a schematic diagram showing a measurement device used in the pressureless DW method. [Figure 10] FIG. 10 shows the results of measuring the amount of liquid absorbed after 30 seconds in the non-pressure DW method. [Figure 11] FIG. 11 is a schematic diagram showing a measuring device used in the volume increase rate measuring test. [Figure 12] FIG. 12 shows the test results of the volume increase rate measurement test. [Figure 13] FIG. 13 is a schematic diagram showing a measuring device used in the volume reduction rate and water separation rate measuring test. [Figure 14] FIG. 14 shows the test results of the volume reduction rate measurement test. [Figure 15] FIG. 15 shows the results of the water release rate measurement test. [Figure 16] Fig. 16A is an SEM photograph of a fracture surface of absorbent A. Fig. 16B is a mapping diagram of Na distribution in the same portion as Fig. 16A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] At least the following points will become apparent from the description of this specification and the accompanying drawings.

[0013] An absorbent article comprising a polymer absorbent having a continuous skeleton and continuous pores, and a skin-side sheet member provided on the skin side of the polymer absorbent, An absorbent article, characterized in that the polymer absorbent has a liquid absorption amount after 30 seconds in a non-pressure DW method of 7.8 ml / g or more and 21.3 ml / g or less.

[0014] According to such an absorbent article, it is possible to realize an absorbent article having a thin absorbent body with appropriate absorption speed performance.

[0015] In such an absorbent article, it is desirable that the volume increase rate of the polymer absorbent when saturated with liquid to the volume before liquid absorption is 233% or more and 567% or less.

[0016] According to such an absorbent article, it is possible to realize an absorbent article having a thinner absorbent body.

[0017] In the above absorbent article, the polymer absorbent is saturated with liquid and has a density of 30 g / cm 2 It is desirable that the volume reduction rate of the volume after the load is applied for 3 minutes relative to the volume at the time of saturated liquid absorption is 34% or more and 48% or less.

[0018] According to such an absorbent article, even if the polymer absorbent absorbs liquid and expands, it is possible for the polymer absorbent to quickly release water under load and return to a thin (compact) state.

[0019] In the above absorbent article, the polymer absorbent is saturated with liquid and has a density of 30 g / cm 2 It is desirable that the water release rate after applying a load for 3 minutes be 65% or more and 72% or less.

[0020] According to such an absorbent article, even if the polymer absorbent absorbs liquid and expands, it is possible for the polymer absorbent to quickly release water under load and return to a thin (compact) state.

[0021] In such an absorbent article, the polymer absorbent is a hydrolysate of a crosslinked polymer of two or more monomers including at least a (meth)acrylic acid ester, and the functional groups desirably have at least one hydrophilic group.

[0022] Such an absorbent article has improved affinity with moisture, and can further improve the absorption rate performance.

[0023] In such an absorbent article, it is desirable that the polymer absorbent is a hydrolysate of a crosslinked polymer of a (meth)acrylic acid ester and a compound containing two or more vinyl groups in one molecule, and contains at least one -COONa group.

[0024] According to such an absorbent article, a continuous skeleton and continuous pores can be easily formed, and a thin absorbent body (absorbent article) can be easily realized.

[0025] Such an absorbent article desirably has a SAP adjacent to the absorbent polymer.

[0026] According to such an absorbent article, the body fluid that has separated from the polymer absorbent can be appropriately absorbed into the other agent (SAP) without substantially impeding the thinning (compactness) of the absorbent body.

[0027] In such an absorbent article, it is desirable that the volume of voids of the pores per unit volume of the polymer absorbent is 85% or more.

[0028] In such an absorbent article, body fluids are easily taken up into the interconnected pores by capillary action, and the article is easily able to absorb body fluids as an absorbent.

[0029] In such an absorbent article, it is preferable that the polymer absorbent contains 0.1 to 30.0% of cross-linked polymer residues.

[0030] According to such an absorbent article, when body fluid is absorbed, the continuous skeleton is stretched, and as the continuous skeleton is stretched, the continuous pores also tend to expand, resulting in a polymer absorbent.

[0031] In such an absorbent article, it is desirable that the average diameter of the interconnected pores is 1 to 1000 μm.

[0032] In such an absorbent article, body fluids are easily taken up into the interconnected pores by capillary action, and the article is easily able to absorb body fluids as an absorbent.

[0033] === Implementation form === As an example of an absorbent article using the absorbent body according to the present embodiment, a so-called pants-type disposable diaper will be described. The absorbent body may be used as an absorbent body for absorbent articles such as not only pants-type disposable diapers but also tape-type disposable diapers, sanitary napkins, absorbent pads, disposable diapers for pets, and absorbent pads for pets. Disposable diapers and absorbent pads can be used for both infants and adults. Body fluids refer to liquids discharged from living organisms including not only humans but also animals. Examples include sweat, urine, feces, menstrual blood, vaginal discharge, breast milk, blood, and exudate.

[0034] ===Basic configuration of pants-type disposable diaper 1=== FIG. 1 is a schematic perspective view of a pants-type disposable diaper 1. FIG. 2A is a schematic plan view of the diaper 1 in an unfolded and stretched state, as viewed from the skin side. FIG. 2B is a schematic cross-sectional view taken along the line XX in FIG. 2A. The "unfolded state" refers to a state in which the diaper 1 is unfolded in a planar manner by separating and opening the joints between the side portion 30a of the ventral member 30 and the side portion 40a of the back member 40 on both sides of the diaper 1. The "stretched state" refers to a state in which the elastic members of the diaper 1 are stretched to such an extent that wrinkles in the diaper 1 are no longer visible. Specifically, the "stretched state" refers to a state in which the dimensions of each member constituting the diaper 1 (for example, the ventral member 30 described later, etc.) are stretched to the extent that the dimensions of the member are equal to or close to the dimensions of the member alone. The CC line in FIG. 2A and FIG. 2B is the center line in the left-right direction. For convenience, the adhesive is omitted in FIG. 2B.

[0035] As shown in FIG. 1, the pants-type diaper 1 has a vertical direction, a horizontal direction, and a front-rear direction, and the diaper 1 is formed with a waist opening BH and a pair of leg openings LH. The vertical direction of the diaper 1 in the unfolded and stretched state in FIG. 2A is referred to as the "longitudinal direction", one side of the longitudinal direction is also referred to as the "ventral side", and the other side is also referred to as the "dorsal side". In the front-rear direction, the side that faces the wearer's ventral side is referred to as the front side, and the side that faces the wearer's back is referred to as the rear side. In addition, the diaper 1 has a thickness direction as shown in FIG. 2B, and the side that contacts the wearer in the thickness direction is referred to as the skin side, and the opposite side is referred to as the non-skin side.

[0036] The diaper 1 is a so-called three-piece type, and includes an absorbent main body 10, an abdominal side member 30, and a back side member 40. The abdominal side member 30 and the back side member 40 are generally rectangular in plan view, with their longitudinal directions aligned with the left-right direction. The abdominal side member 30 covers the abdominal side of the wearer, and the back side member 40 covers the back side of the wearer. The absorbent main body 10 is generally rectangular in plan view. An abdominal end 10ea and a back end 10eb of the absorbent main body 10 are overlapped with the skin-side surfaces of the abdominal side member 30 and the back side member 40, respectively.

[0037] 2A, the diaper 1 in the unfolded and stretched state has a shape symmetrical with respect to the center line CC. The non-skin-side surfaces of the ventral end 10ea and the back end 10eb of the absorbent main body 10 are joined to the skin-side surfaces of the ventral member 30 and the back member 40 with an adhesive or the like (not shown), the absorbent main body 10 is folded in half so that the ventral member 30 and the back member 40 face each other, and both left and right side portions 30a of the ventral member 30 and both left and right side portions 40a of the back member 40 are welded and joined at the side welds SS, thereby forming the diaper 1 into a pants-type diaper.

[0038] The abdominal side member 30 and the back side member 40 each include a skin side sheet 31, 41 and a non-skin side sheet 32, 42 made of soft nonwoven fabric or the like, and a plurality of rubber threads 35, 45 that stretch in the left-right direction. The plurality of rubber threads 35, 45 are arranged side by side at intervals in the up-down direction, and are fixed between the two sheets (31 and 32, 41 and 42) in a state of being stretched in the left-right direction. Therefore, the abdominal side member 30 and the back side member 40 are stretchable in the left-right direction and fit the waist of the wearer.

[0039] The abdominal side member 30 is composed of a skin side sheet 31, a rubber thread 35, and a non-skin side sheet 32 ​​stacked in the thickness direction from the skin side, and joined together with an adhesive such as hot melt. Similarly, the dorsal side member 40 is composed of a skin side sheet 41, a rubber thread 45, and a non-skin side sheet 42 stacked in the thickness direction from the skin side, and joined together with an adhesive such as hot melt.

[0040] The skin side sheets 31, 41 and the non-skin side sheets 32, 42 are each made of a nonwoven fabric, specifically a spunbond nonwoven fabric. However, the present invention is not limited to this, and nonwoven fabrics such as SMS (spunbond / meltblown / spunbond) nonwoven fabrics may be used. In the present embodiment, a single fiber of polypropylene (PP), a thermoplastic resin, is used as the constituent fiber of the nonwoven fabric, but the present invention is not limited to this. For example, a single fiber of other thermoplastic resins such as polyethylene (PE) may be used, or composite fibers having a sheath-core structure such as PE and PP may be used. Furthermore, all of the skin side sheets 31, 41 and the non-skin side sheets 32, 42 do not have to be made of nonwoven fabric, and any one of the skin side sheets 31, 41 or the non-skin side sheets 32, 42 may be made of a soft sheet material other than nonwoven fabric.

[0041] The absorbent body 10 includes a top sheet 13, an absorbent body 11, and a back sheet 15, which are bonded together with an adhesive such as hot melt. The top sheet 13 may be a liquid-permeable sheet, and examples of such sheet include hydrophilic air-through nonwoven fabric and spunbond nonwoven fabric. The back sheet 15 may be a liquid-impermeable sheet, and examples of such sheet include polyethylene film, polypropylene film, and hydrophobic SMS nonwoven fabric. The top sheet 13 and the back sheet 15 are large enough to cover the entire absorbent body 11.

[0042] The absorbent body 10 has leg gathers LG that are provided at the left and right ends and stretch in the longitudinal direction, and three-dimensional gathers LSG that serve as leakage prevention walls for preventing side leakage and are provided on the skin side of the absorbent body 11. The leg gathers LG and three-dimensional gathers LSG each have elastic members 17 and 18 that stretch in the longitudinal direction (up and down direction), respectively.

[0043] The absorbent 11 has a generally rectangular shape in plan view and includes an absorbent core 11c for absorbing liquid. The absorbent core 11c is formed into a generally hourglass shape by wrapping a polymer absorbent (absorbent A) and a superabsorbent polymer (so-called SAP) in a core wrap (specifically, hydrophilic tissue) as an example of a skin-side sheet member. The polymer absorbent (absorbent A) and the superabsorbent polymer (SAP) may each be in a granular form, and it is preferable to use a sieve to make the particles have a particle size within a predetermined range. In the following description, a particulate polymer absorbent (absorbent A) will be described, but is not limited thereto. The polymer absorbent (absorbent A) used in absorbent articles such as the diaper 1 may be in a granular, fine particle, block, sheet, thread, or other form, as appropriate, depending on the state of use.

[0044] ===About polymer absorbents=== The polymer absorbent is a hydrolyzate of a crosslinked polymer of two or more monomers including at least a (meth)acrylic acid ester, and is a polymer compound having at least one hydrophilic group as a functional group. More specifically, it is a hydrolyzate of a crosslinked polymer of a (meth)acrylic acid ester and a compound having two or more vinyl groups in one molecule, and is a polymer compound having at least a -COONa group. The (meth)acrylic acid ester refers to an acrylic acid ester or a methacrylic acid ester. The polymer absorbent is a monolithic organic porous material having at least one or more -COONa groups in one molecule. It may further have a -COOH group. The -COONa groups are distributed approximately uniformly in the skeleton of the porous material.

[0045] The polymer absorbent, which is a hydrolysis product of a crosslinked polymer of (meth)acrylic acid ester and divinylbenzene, has a continuous skeleton formed by an organic polymer having at least -COONa groups, and has interconnected holes (continuous pores) between the skeletons that serve as an absorption field for the liquid to be absorbed. In addition, since the hydrolysis treatment converts the -COOR groups (carboxylate ester groups) of the crosslinked polymer into -COONa groups or -COOH groups (Figure 3), the polymer absorbent may also have -COOR groups. The presence of -COOH groups and -COONa groups in the organic polymer that forms the continuous skeleton can be confirmed by analysis using infrared spectroscopy and a method for quantifying weakly acidic ion exchange groups.

[0046] Fig. 3 is a diagram illustrating the manufacturing process of absorbent A. In Fig. 3, the upper diagram shows the constituent raw materials for polymerization, the middle diagram shows monolith A as a crosslinked polymer of (meth)acrylic acid ester and divinylbenzene, and the lower diagram shows absorbent A obtained by subjecting monolith A in the middle diagram to hydrolysis and drying treatment.

[0047] Hereinafter, a hydrolyzate of a crosslinked polymer of a (meth)acrylic acid ester and divinylbenzene (hereinafter also referred to as "absorbent A") will be described as an example of a polymer absorbent. The polymer absorbent is not limited to absorbent A, and may be a hydrolyzate of a crosslinked polymer of a (meth)acrylic acid ester and a compound containing two or more vinyl groups in one molecule. Furthermore, it may be a hydrolyzate of a crosslinked polymer of two or more monomers including at least a (meth)acrylic acid ester. Hereinafter, "monolith A" refers to an organic porous body consisting of a crosslinked polymer of a (meth)acrylic acid ester and divinylbenzene before hydrolysis treatment, and is also referred to as a "monolithic organic porous body". "Absorbent A" refers to a hydrolyzate of a crosslinked polymer (monolith A) of a (meth)acrylic acid ester and divinylbenzene after hydrolysis treatment and drying treatment. In the following description, absorbent A refers to a dry state.

[0048] The structure of the absorbent A will be described. The absorbent A has a continuous skeleton and continuous pores. The absorbent A, which is an organic polymer forming a continuous skeleton, is obtained by cross-linking polymerization using a (meth)acrylic acid ester as a polymerization monomer and a divinylbenzene as a cross-linking monomer, and hydrolyzing the resulting cross-linked polymer (monolith A), as shown in FIG. 3. The organic polymer forming the continuous skeleton has, as structural units, a polymerized residue of an ethylene group (hereinafter also referred to as "structural unit X") and a cross-linked polymerized residue of divinylbenzene (hereinafter also referred to as "structural unit Y"). The polymerized residue of an ethylene group (structural unit X) in the organic polymer forming the continuous skeleton has a -COONa group, or a -COOH group and a -COONa group, which are generated by hydrolysis of a carboxylic acid ester group. Since the polymerized monomer is a (meth)acrylic acid ester, the polymerized residue of an ethylene group (structural unit X) has a -COONa group, a -COOH group, and an ester group. As a specific example, the production of the absorbent A using butyl methacrylate as a polymerized monomer and divinylbenzene as a cross-linking monomer will be described later.

[0049] In the absorbent A, the ratio of the cross-linked polymer residue of divinylbenzene (structural unit Y) in the organic polymer forming the continuous skeleton is 0.1 to 30 mol %, preferably 0.1 to 20 mol %, based on the total structural units. In the absorbent A in which butyl methacrylate is used as the polymerization monomer and divinylbenzene is used as the cross-linking monomer, the ratio of the cross-linked polymer residue of divinylbenzene (structural unit Y) in the organic polymer forming the continuous skeleton is about 3%, preferably 0.1 to 10 mol %, more preferably 0.3 to 8 mol %, based on the total structural units. If the ratio of the cross-linked polymer residue of divinylbenzene in the organic polymer forming the continuous skeleton is less than the above range, the strength of the absorbent A decreases, and if it exceeds the above range, the absorption amount of the liquid to be absorbed decreases.

[0050] In the absorbent A, the organic polymer forming the continuous skeleton may be composed of only the structural unit X and the structural unit Y, or may have, in addition to the structural unit X and the structural unit Y, a structural unit other than the structural unit X and the structural unit Y, that is, a polymerization residue of a monomer other than (meth)acrylic acid ester and divinylbenzene. Examples of structural units other than the structural unit X and the structural unit Y include polymerization residues of monomers such as styrene, α-methylstyrene, vinyltoluene, vinylbenzyl chloride, (meth)acrylate, isobutene, butadiene, isoprene, chloroprene, vinyl chloride, vinyl bromide, vinylidene chloride, tetrafluoroethylene, (meth)acrylonitrile, vinyl acetate, ethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and trimethylolpropane tri(meth)acrylate. In addition, in the organic polymer forming the continuous skeleton, the proportion of structural units other than the structural unit X and the structural unit Y is 0 to 50 mol%, preferably 0 to 30 mol%, based on the total structural units. In absorbent A, in which butyl methacrylate is used as a polymerization monomer and divinylbenzene is used as a crosslinking monomer, the proportion of structural units other than the structural unit X and the structural unit Y in the organic polymer forming the continuous skeleton is 0 to 50 mol %, and preferably 0 to 30 mol %, relative to all structural units.

[0051] The thickness of the continuous skeleton of absorbent A is 0.1 to 100 μm. If the thickness of the continuous skeleton of absorbent A is less than 0.1 μm, the spaces (pores) for absorbing water in the porous structure may be easily crushed during absorption, which may result in a decrease in the amount of absorption. On the other hand, if the thickness of the continuous skeleton is thicker than 100 μm, the absorption of liquid may be slowed. Since the pore structure of the continuous skeleton of absorbent A is a continuous bubble structure, the thickness of the continuous skeleton is measured by evaluating the cross section of the skeleton that appears on the test piece for electron microscope measurement. The skeleton is often polygonal because it is formed by the gaps between water (water droplets) that are removed by the dehydration and drying process after hydrolysis described later. Therefore, the thickness of the skeleton is the average diameter of the circle circumscribing the polygonal cross section. In rare cases, there may be small holes in the polygon, in which case the circumscribing circle of the polygonal cross section surrounding the small holes is measured.

[0052] The absorbent A has an average diameter of interconnected pores of 1 to 1000 μm. If the average diameter of interconnected pores of absorbent A is less than 1 μm, the porous space (pores) for absorbing water may be easily crushed during absorption, and the absorption rate may decrease. On the other hand, if the average diameter of interconnected pores is thicker than 1000 μm, the liquid absorption rate may decrease. The average diameter of interconnected pores of absorbent A can be measured by mercury intrusion porosimetry, and is the maximum value of the pore distribution curve obtained by mercury intrusion porosimetry. Regarding the sample for measuring the average diameter of interconnected pores, the sample is dried at 50° C. for 18 hours or more in a reduced pressure dryer regardless of the ion form of absorbent A. The final pressure reached is 0 Torr.

[0053] The absorbent A has a structure in which bubble-like macropores overlap each other (see Figs. 4 to 8), and the overlapping parts have an open cell structure (continuous macropore structure) in which common openings (mesopores) have an average diameter of 1 to 1000 µm, preferably 10 to 200 µm, and particularly preferably 20 to 100 µm. Most of them have an open pore structure. The number of overlapping macropores is 1 to 12 in one macropore, and in most cases 3 to 10.

[0054] FIG. 4 is an SEM photograph of absorbent A at a magnification of 50 times. FIG. 5 is an SEM photograph of absorbent A at a magnification of 100 times. FIG. 6 is an SEM photograph of absorbent A at a magnification of 500 times. FIG. 7 is an SEM photograph of absorbent A at a magnification of 1000 times. FIG. 8 is an SEM photograph of absorbent A at a magnification of 1500 times. Absorbent A is an example of absorbent A that uses butyl methacrylate as a polymerization monomer and divinylbenzene as a cross-linking monomer, and absorbent A in FIGS. 4 to 8 is each a cube with a side of 2 mm.

[0055] 4 to 8 show scanning electron microscope (SEM) photographs of examples of absorbent A. The absorbent A shown in Figs. 4 to 8 has a large number of bubble-like macropores, and the bubble-like macropores overlap each other, forming an open-cell structure where the overlapping portions form common openings (mesopores). Most of the open-pore structure is an open pore structure. If the average diameter of the mesopores in a dry state is less than the above range, the absorption rate of the liquid to be absorbed becomes too slow, and if it exceeds the above range, the absorbent A becomes brittle. By making the absorbent A have such an open-cell structure, it is possible to uniformly form macropores and mesopores, and to remarkably increase the pore volume and specific surface area compared to particle agglomeration type porous bodies such as those described in JP-A-8-252579.

[0056] The total pore volume of the pores (voids) of the absorbent A is preferably 1 to 50 ml / g, and more preferably 2 to 30 ml / g. If the total pore volume of the absorbent A is less than 0.5 ml / g, the spaces (voids) for absorbing water in the porous material are likely to collapse during absorption, and the amount of absorption and the absorption rate may decrease. If it exceeds 50 ml / g, the strength of the absorbent A decreases. The total pore volume can be measured by mercury intrusion porosimetry. The sample for measuring the total pore volume is absorbent A that has been dried in a vacuum dryer at a temperature of 50°C for 18 hours or more, regardless of the ion form of the absorbent A. The final pressure reached is 0 Torr.

[0057] Hereinafter, the state when the absorbent A comes into contact with a liquid such as a body fluid (hereinafter also referred to as "body fluid") will be described, but the same applies when the absorbent 11 containing the absorbent A comes into contact with a body fluid. In addition, since the weight of absorbed body fluid is approximately proportional to the amount of body fluid, hereinafter, the weight of body fluid will also be referred to as the "amount of body fluid".

[0058] First, when body fluid comes into contact with absorbent A, it is absorbed into the pores (voids) of absorbent A by capillary action. As shown in Figs. 4 to 8, the continuous pores of absorbent A are pores in which a plurality of pores (voids) are interconnected, and it is possible to visually confirm from the outside that a large number of voids are provided. A certain amount of body fluid enters the large number of pores by capillary action, and absorbent A absorbs the body fluid. Of the certain amount of body fluid absorbed by absorbent A, a portion is absorbed into the continuous skeleton by osmotic pressure, and the continuous skeleton is extended. Of the certain amount of body fluid absorbed by absorbent A, the body fluid that is not absorbed into the continuous skeleton is absorbed while remaining within the pores.

[0059] Absorbent A has a property that the continuous skeleton extends when it absorbs liquid. This extension of the continuous skeleton extends in almost all directions. As the external shape of absorbent A increases due to the extension of the continuous skeleton, the size of each pore also increases. When the size of the pore increases, the volume of the pore increases, and the amount of body fluid that can be retained in the pore increases. In other words, absorbent A that has absorbed a certain amount of body fluid and become large can absorb a further predetermined amount of body fluid by capillary action. In addition, since absorbent A absorbs body fluid by capillary action, absorbent A can quickly absorb body fluid. Note that, with respect to the body fluid absorbed by absorbent A, the amount of body fluid retained in the pores is greater than the body fluid absorbed by the continuous skeleton.

[0060] Thus, most of the body fluid absorption by absorbent A is achieved by retaining the body fluid within the pores due to capillary action, so the greater the porosity (the volume of the pores relative to the volume of absorbent A), which is the ratio of the volume of the pores (total pore volume), the more body fluid can be absorbed. It is preferable that this porosity is 85% or more.

[0061] Determine the porosity of absorbent A. The specific surface area of ​​absorbent A obtained by mercury intrusion porosimetry is 400 m 2 / g, and the pore volume is 15.5ml / g. This pore volume of 15.5ml is the volume of the pores in 1g of absorbent A. If we assume that the specific gravity of absorbent A is 1g / ml, then the volumes that they occupy in 1g of absorbent A are 15.5ml of pore volume and 1ml of absorbent A. The total volume (volume) of 1g of absorbent A is 15.5+1[ml], and the ratio of the pore volume to that is the porosity. As a result, the porosity is 15.5 / (15.5+1)×100 ≒ 94%.

[0062] In addition, this polymer absorbent (absorbent A) has an absorption speed performance (initial liquid absorption speed) equal to or higher than that of pulp fiber. The non-pressure DW (Demand Wettability) method is generally well known as a measurement method for evaluating the absorption speed of absorbents. This non-pressure DW method is described, for example, in JP 2018-39944 A. The amount of liquid absorbed after 30 seconds (amount of liquid absorbed after 30 seconds) of the polymer absorbent in the non-pressure DW method is 7.8 ml / g or more and 21.3 ml / g or less, which is equal to or higher than the amount of liquid absorbed after 30 seconds (6.8 ml / g) of pulp fiber.

[0063] A specific description will be given below with reference to Figs. 9 and 10. Fig. 9 is a schematic diagram showing a measuring device used in the non-pressurized DW method. Fig. 10 will be described later. As described above, the non-pressurized DW method is a common method, so the description of the non-pressurized DW method according to this embodiment follows the description in JP 2018-39944 A. However, since there are some differences, the non-pressurized DW method according to the present invention will be defined by clarifying those differences.

[0064] The non-pressurized DW method is a measurement method performed in a room at 25°C and 50% humidity using a non-pressurized DW method measuring device 50 shown in Fig. 9. The non-pressurized DW method measuring device 50 shown in Fig. 9 is composed of a burette part 52 (scale capacity 50 ml, length 86 cm, inner diameter 1.05 cm), a conduit (inner diameter 7 mm), and a measurement stand 56. The burette part 52 is connected to a rubber stopper 51 at the top and an air introduction tube 59 (tip inner diameter 3 mm) and a cock 57 at the bottom, and further, a cock 58 is provided at the top of the air introduction tube 59. A conduit is attached from the burette part 52 to the measurement stand 56. A hole with a diameter of 3 mm is provided in the center of the measurement stand 56 as a saline supply part, and a conduit is connected to it.

[0065] Using the non-pressurized DW method measuring device 50 having this configuration, first close the cock 57 of the burette part 52 and the cock 58 of the air introduction tube 59, pour in saline solution 53 (NaCl aqueous solution) with a salt concentration of 0.9% by weight adjusted to 25°C from the top of the burette part 52, plug the top of the burette with a rubber plug 51, and then open the cock 57 of the burette part 52 and the cock 58 of the air introduction tube 59. Next, wipe off the saline solution 53 that has overflowed onto the measurement table 56, and then adjust the height of the measurement table 56 so that the top surface of the measurement table 56 and the water level of the saline solution 53 coming out of the conduit port in the center of the measurement table 56 are at the same height. While wiping off the saline solution 53 from the saline solution supply part, adjust the water level of the saline solution 53 in the burette part 52 to the top of the burette part 52 scale (0 ml line).

[0066] Next, the cock 57 of the burette part 52 and the cock 58 of the air introduction tube 59 are closed, and a tissue 55 made of 100% wood pulp (basis weight 15±1 gsm, measured pressure 3 g / cm by a nonwoven fabric thickness meter) is placed on the measurement table 56 so that the saline supply part is in the center. 2 A tissue 55 (thickness at time of measurement: 0.1±0.02 mm) is placed on the tissue, and then the test object (polymer absorbent) is placed on the tissue 55, centered on the saline supply part of the measurement table 56. The test object is placed in a cylindrical container 54, and its periphery is constrained by the container 54. Then, the cock 57 of the burette part 52 and the cock 58 of the air introduction tube 59 are opened.

[0067] The measurement start time is the time when the test object starts to absorb liquid and the first bubble introduced from the air introduction tube 59 reaches the water level of the physiological saline 53 in the burette part 52 (the time when the water level of the physiological saline 53 in the burette part 52 drops), and the amount of reduction in the physiological saline 53 in the burette part 52 (the amount of physiological saline absorbed by the test object) M (ml) is continuously read. The amount of absorption of the test object after a predetermined time has elapsed (in this embodiment, after 30 seconds has elapsed) from the start of absorption is calculated by the DW method: Absorption amount (ml / g) = M ÷ weight (g) of the test object.

[0068] As also shown in JP 2018-39944 A, in the non-pressurized DW method, a mesh is usually placed on the measurement table 56, and the test object is placed on the mesh. In contrast, in this embodiment, in order to conduct the test in a situation close to that of an actual absorbent article (diaper 1), the above-mentioned tissue 55 is placed instead of the mesh. That is, in the non-pressurized DW method according to the present invention, a mesh with a basis weight of 15±1 gsm and a measurement pressure of 3 g / cm using a nonwoven fabric thickness gauge are placed between the measurement table 56 and the test object (polymer absorbent). 2 This test method is performed by sandwiching a tissue 55 made of 100% wood pulp with a thickness of 0.1±0.02 mm at the time.

[0069] FIG. 10 is a diagram showing the measurement results of the amount of liquid absorbed after 30 seconds in the non-pressure DW method. Four polymer absorbents were prepared as the polymer absorbent, pulp fiber as a comparative example, and Infinity particles as a reference example, and the amount of liquid absorbed after 30 seconds in the non-pressure DW method was measured using each of them as a test object. Here, the Infinity particles are absorbents manufactured by P&G and have a structure (foam structure) similar to that of polymer absorbents. However, unlike polymer absorbents, they do not have the function of absorbing liquid and expanding.

[0070] The liquid absorption amount of the polymer absorbent after 30 seconds in the non-pressure DW method was 7.8 ml / g or more and 21.3 ml / g or less, which is equal to or greater than the liquid absorption amount after 30 seconds of pulp fiber (6.8 ml / g) and significantly greater (good) than the liquid absorption amount after 30 seconds of Infinity particle body (2.3 ml / g).

[0071] As described above, the polymer absorbent is applied to an absorbent article (absorbent body 11), and therefore the absorbent article (diaper 1) according to the present embodiment is specified as follows. That is, the absorbent article (diaper 1) has a polymer absorbent having a continuous skeleton and continuous pores, and a tissue provided on the skin side of the polymer absorbent, and the polymer absorbent has a liquid absorption amount after 30 seconds in a non-pressure DW method of 7.8 ml / g or more and 21.3 ml / g or less. Therefore, as described below, it is possible to realize an absorbent article having a thin absorbent body 11 with appropriate absorption speed performance.

[0072] 2. Description of the Related Art Absorbent articles using absorbent bodies that combine SAP, which has a high absorption capacity, with pulp fibers, which has a high absorption rate, have been known.

[0073] However, when SAP is combined with pulp fibers, the large amount of pulp in the pulp fibers causes the absorbent body to become bulky (problem of not being able to be made thin), which is undesirable from the viewpoints of distribution, storage, portability, wearing comfort (uncomfortable wearing, poor breathability), etc.

[0074] On the other hand, if the pulp fiber is removed and only SAP is used, the excellent absorption speed performance of the pulp fiber is not exhibited, resulting in an absorbent with a slow absorption speed. Furthermore, if the absorption surface is increased to compensate for the slow absorption speed, other problems such as leakage, discomfort when worn, and increased skin stress may occur.

[0075] In contrast, in the absorbent article (diaper 1) according to the present embodiment, a polymer absorbent having a continuous skeleton and continuous pores is used instead of pulp fibers, and this structure makes it possible to make the absorbent 11 (and therefore the absorbent article) thinner (particularly, to make the absorbent 11 thinner before absorbing liquid (before expanding)). Furthermore, a polymer absorbent having a liquid absorption amount after 30 seconds in the non-pressure DW method of 7.8 ml / g to 21.3 ml / g is used instead of pulp fibers, making it possible to obtain an absorption speed performance equal to or higher than that when pulp fibers are used (quickly drawing in body fluids from the tissue).

[0076] Therefore, according to this embodiment, it is possible to realize an absorbent article including a thin absorbent body 11 having appropriate absorption speed performance.

[0077] As described above, the polymer absorbent according to the present embodiment is a hydrolysate of a cross-linked polymer of two or more monomers including at least a (meth)acrylic acid ester, and has at least one hydrophilic group as a functional group.

[0078] This improves the affinity for moisture, making it possible to further improve the absorption rate performance.

[0079] Furthermore, the polymer absorbent according to the present embodiment is a hydrolysate of a crosslinked polymer of a (meth)acrylic acid ester and a compound containing two or more vinyl groups in one molecule, and contains at least one -COONa group.

[0080] This makes it easier to form a continuous skeleton and continuous pores, and makes it possible to easily realize a thin absorbent body 11 (absorbent article).

[0081] As described above, when bodily fluids enter the continuous pores of the polymer absorbent due to capillary action, the continuous skeleton of the polymer absorbent absorbs a part of the bodily fluid due to osmotic pressure and expands. This expansion enlarges the pores and further absorbs the bodily fluid. That is, the polymer absorbent absorbs bodily fluids while expanding (increasing in volume) (in other words, it can expand to increase the amount of fluid it can hold). This makes it possible to make the polymer absorbent (absorbent body 11) thinner before absorbing bodily fluids (before expanding). In order to consider this issue, the following test (hereinafter referred to as the volume increase rate measurement test) was conducted to measure the volume increase rate of the polymer absorbent when saturated with liquid compared to the volume before liquid absorption.

[0082] A specific description will be given below with reference to Figures 11 and 12. Figure 11 is a schematic diagram showing a measuring device used in a volume increase rate measurement test. Figure 12 will be described later.

[0083] 11 is composed of a test object storage container 61 and a petri dish 62. The test object storage container 61 is an acrylic cylindrical member having openings at the top and bottom ends, with a nylon mesh (not shown) attached to the bottom end.

[0084] The cylindrical member has an inner diameter of 26 mm, a length of 80 mm, an outer diameter of 38 mm, and a weight of 57 g. The nylon mesh used is N-N0255HD 115 manufactured by NBC Meshtec. The petri dish 62 is a container having an inner diameter of 97 mm and a weight of 58 g.

[0085] Then, the test object 63 is placed into the test object storage container 61 from the upper end (opening), and the height of the placed test object 63 is measured. Then, the calculation formula (volume=bottom area(3.14×(inner diameter(26 mm) / 2) 2 The volume of the test object 63 is calculated by multiplying the length by the height of the test object 63 by the length of the test object 63 x the height of the test object 63, and this volume is defined as the volume before liquid absorption. Note that the upper end of the test object 63 may be slightly curved, and in this case, the height of the topmost part is measured. In addition, the weight of the test object container 61 containing the test object 63 is measured in advance for the water-repelling rate measurement test described later.

[0086] Next, 60 cc of physiological saline (NaCl aqueous solution) with a salt concentration of 0.9% by weight is placed in a petri dish 62, and a test object storage container 61 containing a test object 63 (whose volume has been measured before absorbing liquid) is placed in the petri dish 62 (see FIG. 11). Then, the test object 63 starts to absorb the physiological saline through the nylon mesh, and the height (volume) of the test object 63 changes. This change in height (volume) is continuously observed visually, and when the height becomes stable (i.e., when the test object 63 has absorbed liquid to saturation), the height of the test object 63 is measured. Then, the volume of the test object 63 is calculated using the above formula, and this is defined as the volume at saturation when absorbing liquid. In this embodiment, since it has been confirmed that the height of the test object 63 becomes stable two and a half minutes after the start of absorbing liquid, the height is measured two and a half minutes later. In addition, when the upper end of the test object 63 is slightly curved, the height of the topmost part is measured in the same manner as in the measurement before absorbing liquid. In addition, for the purpose of a water-repelling rate measurement test described later, the weight of the test object storage container 61 containing the test object 63 that has absorbed liquid to saturation is measured.

[0087] FIG. 12 is a diagram showing the test results of the volume increase rate measurement test. Three polymer absorbents were prepared as the polymer absorbent, pulp fiber as a comparative example, and Infinity particles as a reference example, and the pre-absorption volume and the saturated absorption volume were measured for each of them as the test object 63 (the test was performed three times for each test object 63). Then, the volume increase rate of the saturated absorption volume to the pre-absorption volume was calculated (as will be described later, in the comparative example and the reference example, the volume has decreased, so it is the volume decrease rate. Both are collectively called the volume change rate). That is, the volume change rate is calculated by the saturated absorption volume ÷ the pre-absorption volume, and for example, in the case of the first pulp fiber in FIG. 12, it is 13.3 ÷ 15.9 = 0.83, so it is 83%.

[0088] The volume change rate of the polymer absorbent is 233% to 567%, while the volume change rates of the pulp fiber and Infinity particle body are 83% to 85% and 60% to 66%, respectively. In other words, the pulp fiber and Infinity particle body are decreasing in volume (shrinking) due to liquid absorption, while the polymer absorbent is increasing in volume (expanding).

[0089] Thus, the absorbent article (diaper 1) in this embodiment uses a polymer absorbent whose volume increase rate at saturated absorption relative to the volume before absorption is 233% to 567%. In other words, since a polymer absorbent that absorbs body fluids while expanding (increasing in volume) is used, the polymer absorbent (absorber 11) before absorbing body fluids (before expanding) can be made thinner, making it possible to realize a thinner absorbent article (diaper 1).

[0090] As described above, the polymer absorbent (absorbent A) absorbs bodily fluids while expanding (increasing in volume) (expanding to increase the amount of fluid retained), but when a load (pressure) is applied to the polymer absorbent (for example, when pressure is applied by the wearer who is wearing the diaper 1 when he or she moves), the polymer absorbent contracts (decreases in volume) and releases bodily fluids to the outside (hereinafter, for convenience, referred to as "separation"). For example, SAP that may be used in the absorber 11 together with the polymer absorbent hardly releases water even when pressure is applied once the polymer absorbent has absorbed bodily fluids, but the polymer absorbent has the property of easily releasing water while contracting (decreasing in volume). In order to consider such matters, the following test (hereinafter, referred to as "volume reduction rate and water release rate measurement test") for measuring the volume reduction rate and water release rate when a load is applied to the polymer absorbent was performed following the above-mentioned volume increase rate measurement test.

[0091] A specific description will be given below with reference to Figs. 13 to 15. Fig. 13 is a schematic diagram showing a measuring device (hereinafter referred to as a volume reduction rate measuring device 70) used in the volume reduction rate and water separation rate measuring test. Figs. 14 and 15 will be described later.

[0092] The volume reduction rate etc. measuring device 70 shown in FIG. 13 includes a pressurizing member 71 and underlying filter paper 74 in addition to the above-mentioned test subject storage container 61.

[0093] The pressurizing member 71 includes a pressing member 72 that contacts and presses the test object 63 (polymer absorbent) and a weight 73 that is placed on the pressing member 72. The pressing member 72, like the test object storage container 61, is an acrylic cylindrical member with openings at the top and bottom, with a nylon mesh attached to the bottom. The cylindrical member has an inner diameter of 19.5 mm, a length of 120 mm, an outer diameter of 25.5 mm, and a weight of 28 g. As with the test object storage container 61, the nylon mesh used is N-N0255HD 115 manufactured by NBC Meshtec.

[0094] The weight 73 is a weight having an acrylic cylindrical member (diameter 25 mm, length 8 mm) and a weighting filter paper attached to the bottom thereof, and its weight is 124 g.

[0095] Then, by placing a weight 73 on the pressing member 72, a total of 152 g (30 g / cm 2 The pressure member 71 is formed with a pressure of 30 g / cm 2 This figure is based on the estimated pressure exerted when a person wearing the diaper 1 moves.

[0096] The underlying filter paper 74 is located at the bottom and is used to place the test subject storage container 61. For this underlying filter paper 74, FILTERPAPER manufactured by ADVANTEC is used.

[0097] The volume reduction rate and water release rate measurement test is performed following the volume increase rate measurement test. The test object storage container 61 containing the test object 63 that has absorbed liquid to saturation is removed from the petri dish 62, and the test object storage container 61 is placed on the underlying filter paper 74. Before placing the test object storage container 61 on the underlying filter paper 74, the weight of the underlying filter paper 74 is measured.

[0098] Then, the pressure member 71 is placed on the test object 63. That is, the pressing member 72 is inserted into the test object storage container 61 so that the nylon mesh is on the lower side. Then, the pressing member 72 is positioned on the test object 63 with the nylon mesh in contact with the test object 63. Then, when the loading weight 73 is placed on the pressing member 72, the weight of the pressing member 72 and the loading weight 73 is applied to the test object 63.

[0099] Then, the physiological saline solution absorbed in the test object 63 starts to separate into the underlying filter paper 74 through the nylon mesh of the test object storage container 61, and the height (volume) of the test object 63 changes (decreases). Then, the height is measured 3 minutes after the load is applied. From the height, the volume of the test object 63 is calculated using the above formula, and this is calculated as 30 g / cm for the test object 63 saturated with liquid. 2 The volume after the load is applied for 3 minutes is called the post-load volume. Note that if the upper end of the test object 63 is slightly curved, the height of the top is measured in the same manner as in the measurement before liquid absorption.

[0100] In addition, 3 minutes after the load is applied, the weight of the underlying filter paper 74 is also measured together with the height. The weight of the underlying filter paper 74 before the load is applied is subtracted from the measured weight, and the obtained value is used as the weight of the test object 63 saturated with liquid (30 g / cm 2 The amount of water released is measured after applying a load for 3 minutes.

[0101] Fig. 14 is a diagram showing the test results of the volume reduction rate measurement test. The same three polymer absorbents as those in the volume increase rate measurement test were used as the test objects 63 to measure the volumes after loading (each test object 63 was tested three times). Then, the volume reduction rate of the volume after loading relative to the volume at saturated liquid absorption (already obtained in the volume increase rate test, see Fig. 12) was obtained. As shown in Fig. 14, the volume reduction rate of the polymer absorbent was 34% or more and 48% or less, and the volume of the polymer absorbent was less than half (remarkably reduced).

[0102] FIG. 15 shows the results of the water release ratio measurement test. As in the volume reduction ratio measurement test, the three polymer absorbents were used as test objects 63, and the water release ratio was measured (each test object 63 was tested three times). The water release ratio was calculated as the ratio of the water release ratio to the amount of absorption. As described above, the weight of the test object container 61 containing the test object 63 was measured before and after absorption during the volume increase ratio measurement test, and the amount of absorption was calculated by taking the difference between the weights. As shown in FIG. 15, the water release ratio was 65% or more and 72% or less, and more than half of the samples released water (remarkable water release. Note that the water release ratio of SAP is said to be about 40% at most).

[0103] In this manner, in the absorbent article (diaper 1) according to the present embodiment, the polymer absorbent that has absorbed the liquid to saturation is filled with 30 g / cm 2 The polymer absorbent used has a volumetric reduction rate of 34% to 48% after applying a load for 3 minutes compared to the volume at saturation. 2 A polymer absorbent having a water release rate of 65% to 72% after a load is applied for 3 minutes is used. In other words, since a polymer absorbent that significantly releases water and significantly reduces in volume when a load is applied is used, even if the polymer absorbent (absorbent body 11) absorbs liquid once and expands, it can quickly release water under the load and return to a thin state (compact state) (once it becomes thin, it can absorb liquid again).

[0104] As described above, the absorbent article (diaper 1) according to this embodiment has SAP that can be adjacent to the polymer absorbent. That is, the absorbent 11 includes the polymer absorbent and SAP, and SAP has a higher liquid retention capacity (liquid retention property) and is less likely to expand than the polymer absorbent, so that the body fluid that has separated from the polymer absorbent can be appropriately absorbed (passed on) to another agent (SAP) without substantially impeding the thinning (compactness) of the absorbent 11.

[0105] ===About the manufacturing method of absorbent A=== The absorbent A can be obtained through a cross-linking polymerization step and a hydrolysis step, as shown in Fig. 3. The method for producing the absorbent A will be described below.

[0106] First, an oil-soluble monomer for crosslinking polymerization, a crosslinkable monomer, a surfactant, water, and optionally a polymerization initiator are mixed to obtain a water-in-oil emulsion, which is an emulsion in which the oil phase is the continuous phase and water droplets are dispersed therein.

[0107] As shown in the upper diagram of Figure 3, absorbent A is formed by cross-linking polymerization of monolith A using butyl methacrylate as the (meth)acrylic acid ester as the oil-soluble monomer, divinylbenzene as the cross-linking monomer, sorbitan monooleate as the surfactant, and isobutyronitrile as the polymerization initiator.

[0108] For absorbent A, as shown in the upper diagram of Figure 3, first, 9.2 g of t-butyl methacrylate as an oil-soluble monomer, 0.28 g of divinylbenzene as a cross-linking monomer, 1.0 g of sorbitan monooleate (hereinafter abbreviated as SMO) as a surfactant, and 0.4 g of 2,2'-azobis(isobutyronitrile) as a polymerization initiator are mixed and dissolved uniformly.

[0109] Next, the t-butyl methacrylate / divinylbenzene / SMO / 2,2'-azobis(isobutyronitrile) mixture is added to 180 g of pure water and stirred under reduced pressure using a planetary stirring device, a vacuum stirring and degassing mixer (manufactured by EME), to obtain a water-in-oil emulsion.

[0110] The emulsion is then quickly transferred to a reaction vessel, sealed, and polymerized at 60°C for 24 hours under static conditions. After polymerization is complete, the contents are removed, extracted with methanol, and dried under reduced pressure to obtain monolith A having a continuous macropore structure. The internal structure of monolith A was observed by SEM. Figure 16A is an SEM photograph of the fracture surface of absorbent A. Figure 16B is a mapping diagram of Na distribution in the same portion as Figure 16A. Monolith A has a continuous cell structure, and the thickness of the continuous skeleton was 5.4 μm. The average diameter measured by mercury intrusion porosimetry was 36.2 μm, and the total pore volume was 15.5 mL / g.

[0111] The content of divinylbenzene in the total monomers is preferably 0.3 to 10 mol%, more preferably 0.3 to 5 mol%. The ratio of divinylbenzene to the total of butyl methacrylate and divinylbenzene is preferably 0.1 to 10 mol%, more preferably 0.3 to 8 mol%. In absorbent A, the ratio of butyl methacrylate to the total of butyl methacrylate and divinylbenzene is 97.0 mol%, and the ratio of divinylbenzene is 3.0 mol%.

[0112] The amount of surfactant added varies greatly depending on the type of oil-soluble monomer and the size of the desired emulsion particles (macropores), but is preferably in the range of about 2 to 70% of the total amount of the oil-soluble monomer and surfactant.

[0113] In addition, in order to control the bubble shape and size of Monolith A, alcohols such as methanol and stearyl alcohol, carboxylic acids such as stearic acid, hydrocarbons such as octane, dodecane, and toluene, and cyclic ethers such as tetrahydrofuran and dioxane may be coexisted in the system.

[0114] There is no particular restriction on the mixing method when forming a water-in-oil emulsion. A mixing method such as a method of mixing each component at once all at once, a method of dissolving oil-soluble components such as an oil-soluble monomer, a surfactant, and an oil-soluble polymerization initiator, and a water-soluble component such as water or a water-soluble polymerization initiator separately and then mixing each component can be adopted. There is no particular restriction on the mixing device for forming the emulsion, and in order to obtain the desired emulsion particle size, an appropriate device can be selected from a normal mixer, a homogenizer, a high-pressure homogenizer, and a so-called planetary mixing device in which the material to be processed is placed in a mixing container and rotated around the revolution axis while being tilted, thereby stirring and mixing the material to be processed. There is also no particular restriction on the mixing conditions, and the stirring rotation speed and stirring time can be set arbitrarily to obtain the desired emulsion particle size. Among these mixing devices, a planetary mixing device can uniformly generate water droplets in a W / O emulsion, and the average diameter can be arbitrarily set within a wide range.

[0115] The polymerization conditions for polymerizing the water-in-oil emulsion can be selected from various conditions depending on the type of monomer and the initiator system. For example, when azobisisobutyronitrile, benzoyl peroxide, potassium persulfate, etc. are used as the polymerization initiator, the polymerization can be carried out by heating in a sealed container under an inert atmosphere at 30 to 100°C for 1 to 48 hours. When hydrogen peroxide-ferrous chloride, sodium persulfate-acidic sodium sulfite, etc. are used as the polymerization initiator, the polymerization can be carried out in a sealed container under an inert atmosphere at 0 to 30°C for 1 to 48 hours. After the polymerization is completed, the contents are taken out and subjected to Soxhlet extraction with a solvent such as isopropanol to remove unreacted monomers and residual surfactants, thereby obtaining monolith A shown in the middle diagram of Figure 3.

[0116] Next, the monolith A (crosslinked polymer) is hydrolyzed to obtain absorbent A. The monolith A is immersed in dichloroethane containing zinc bromide and stirred at 40°C for 24 hours, and then contacted with methanol, 4% hydrochloric acid, 4% aqueous sodium hydroxide solution, and water in that order to hydrolyze the monolith A. After drying, the block-shaped absorbent A is crushed to a specified size to obtain particulate absorbent A.

[0117] There is no particular limitation on the method of hydrolysis of monolith A, and it can be carried out by various methods. For example, aromatic solvents such as toluene and xylene, halogen-based solvents such as chloroform and dichloroethane, ether-based solvents such as tetrahydrofuran and isopropyl ether, amide-based solvents such as dimethylformamide and dimethylacetamide, alcohol-based solvents such as methanol and ethanol, carboxylic acid-based solvents such as acetic acid and propionic acid, or water can be used as a solvent, and the solvent can be contacted with a strong base such as sodium hydroxide, a hydrohalic acid such as hydrochloric acid, a Bronsted acid such as sulfuric acid, nitric acid, trifluoroacetic acid, methanesulfonic acid, and p-toluenesulfonic acid, or a Lewis acid such as zinc bromide, aluminum chloride, aluminum bromide, titanium (IV) chloride, cerium chloride / sodium iodide, and magnesium iodide.

[0118] Among the polymerization raw materials of the organic polymer forming the continuous skeleton of the absorbent A, the (meth)acrylic acid ester is not particularly limited, but is preferably a C1-C10 alkyl ester of (meth)acrylic acid, and more preferably a C4 alkyl ester of (meth)acrylic acid. Examples of the C4 alkyl ester of (meth)acrylic acid include t-butyl (meth)acrylic acid ester, n-butyl (meth)acrylic acid ester, and iso-butyl (meth)acrylic acid ester.

[0119] The monomers used in the crosslinking polymerization may be only (meth)acrylic acid esters and divinylbenzene, or may contain other monomers other than (meth)acrylic acid esters and divinylbenzene in addition to (meth)acrylic acid esters and divinylbenzene. Examples of other monomers include styrene, α-methylstyrene, vinyltoluene, vinylbenzyl chloride, (meth)acrylate glycidyl, (meth)acrylate 2-ethylhexyl, isobutene, butadiene, isoprene, chloroprene, vinyl chloride, vinyl bromide, vinylidene chloride, tetrafluoroethylene, (meth)acrylonitrile, vinyl acetate, ethylene glycol di(meth)acrylate, and trimethylolpropane tri(meth)acrylate. In the total monomers used in the crosslinking polymerization, the proportion of monomers other than (meth)acrylic acid esters and divinylbenzene is preferably 0 to 80 mol%, more preferably 0 to 50 mol%.

[0120] The surfactant is not limited to sorbitan monooleate. Any surfactant may be used as long as it can form a water-in-oil type (W / O) emulsion when the crosslinking polymerization monomer is mixed with water. For example, nonionic surfactants such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan trioleate, polyoxyethylene nonylphenyl ether, polyoxyethylene stearyl ether, and polyoxyethylene sorbitan monooleate, anionic surfactants such as potassium oleate, sodium dodecylbenzenesulfonate, and dioctyl sodium sulfosuccinate, cationic surfactants such as distearyl dimethyl ammonium chloride, and amphoteric surfactants such as lauryl dimethyl betaine can be used. These surfactants may be used alone or in combination of two or more.

[0121] As the polymerization initiator, a compound that generates radicals by heat and light irradiation is preferably used. The polymerization initiator may be water-soluble or oil-soluble, and examples thereof include azobis(4-methoxy-2,4-dimethylvaleronitrile), azobisisobutyronitrile, azobisdimethylvaleronitrile, azobiscyclohexanenitrile, azobiscyclohexanecarbonitrile, azobis(2-methylpropionamidine)dihydrochloride, benzoyl peroxide, potassium persulfate, ammonium persulfate, hydrogen peroxide-ferrous chloride, sodium persulfate-acidic sodium sulfite, and tetramethylthiuram disulfide. However, in some cases, there are systems in which polymerization proceeds only by heating or light irradiation without the addition of a polymerization initiator, and in such systems, the addition of a polymerization initiator is not necessary.

[0122] ===Other embodiments=== Although the embodiment of the present invention has been described above, the above embodiment is intended to facilitate understanding of the present invention and is not intended to limit the present invention. Furthermore, the present invention may be modified or improved without departing from the spirit of the present invention, and it goes without saying that the present invention includes equivalents. For example, the following modifications are possible.

[0123] In the above embodiment, a tissue is used as an example of the skin-side sheet member provided on the skin side of the polymer absorbent, but the present invention is not limited to this. For example, a hydrophilic nonwoven fabric may be used.

[0124] In the above embodiment, the skin side sheet member is a core wrap that encases the polymer absorbent (absorbent A) and SAP and constitutes the absorbent 11 together with the polymer absorbent (absorbent A) and SAP, but this is not limited to the above. For example, there may be no core wrap encasing the polymer absorbent (absorbent A) and SAP (in such a case, the top sheet 13 corresponds to the skin side sheet member).

[0125] In other words, the skin side sheet member may have a function of temporarily receiving liquid and transferring it to the polymer absorbent (absorbent A).

[0126] In the above embodiment, the absorbent 11 is described as comprising a polymer absorbent (absorbent A) and SAP, but this is not limited thereto. The absorbent 11 may be composed only of a polymer absorbent (absorbent A). Furthermore, the substance used together with the polymer absorbent (absorbent A) is not limited to SAP. For example, the absorbent 11 may comprise a polymer absorbent (absorbent A) and pulp fibers, or may comprise a polymer absorbent (absorbent A), SAP, and pulp fibers. [Explanation of symbols]

[0127] 1 Diapers (pants-type disposable diapers, absorbent articles), 10 absorbent body, 10ea end, 10eb end, 11 absorbent body, 11c absorbent core, 13 top sheet, 15 back sheet, 17 elastic member, 18 elastic member, 30 abdominal member, 30a side portion, 31 skin side sheet, 32 non-skin side sheet, 35 rubber thread, 40 back member, 40a side portion, 41 skin side sheet, 42 non-skin side sheet, 45 rubber thread, 50 Non-pressure DW method measuring device, 51 Rubber stopper, 52 Burette part, 53 Physiological saline, 54 Container, 55 Tissue, 56 Measurement table, 57 faucet, 58 faucet, 59 air introduction tube, 60 Volume increase rate measuring device, 61 Test object container, 62 Petri dish, 63 test object, 70 Volume reduction rate measuring device, 71 Pressurizing member, 72 Pressing member, 73 Weight for weighting, 74 Filter paper for underlay, SS welded parts, LH leg opening, BH waist opening

Claims

1. An absorbent article comprising a polymer absorbent having a continuous skeleton and continuous pores, and a skin-side sheet member provided on the skin side of the polymer absorbent, The absorbent article is characterized in that the polymer absorbent has a liquid absorption amount after 30 seconds in a non-pressure DW method of 7.8 ml / g or more and 21.3 ml / g or less.

2. An absorbent article comprising a polymer absorbent having a continuous skeleton and continuous pores, and a skin-side sheet member provided on the skin side of the polymer absorbent, The polymer absorbent has a liquid absorption amount after 30 seconds in a non-pressure DW method of 12.7 ml / g or more; The polymer absorbent saturated with liquid was applied with 30 g / cm 2 An absorbent article characterized in that the volume reduction rate of the volume after a load is applied for 3 minutes to the volume at saturation of liquid absorption, which is the volume at saturation of liquid absorption, is 34% or more.

3. The absorbent article according to claim 1 or 2, An absorbent article characterized in that a volume increase rate of the polymer absorbent when saturated with liquid, that is, a volume of the polymer absorbent when saturated with liquid, relative to the volume before liquid absorption is 233% or more and 567% or less.

4. The absorbent article according to claim 3, The polymer absorbent saturated with liquid was applied with 30 g / cm 2 An absorbent article, characterized in that a volume reduction rate of a volume after a load is applied for 3 minutes is 34% or more and 48% or less relative to the volume at the time of saturated liquid absorption.

5. The absorbent article according to claim 3 or claim 4, The polymer absorbent saturated with liquid was applied with 30 g / cm 2 An absorbent article having a water release rate of 65% or more and 72% or less after a load is applied for 3 minutes.

6. The absorbent article according to any one of claims 1 to 5, The absorbent article is characterized in that the polymer absorbent is a hydrolysate of a crosslinked polymer of two or more monomers including at least a (meth)acrylic acid ester, and the functional groups have at least one hydrophilic group.

7. 7. The absorbent article according to claim 6, The polymer absorbent is a hydrolyzate of a crosslinked polymer of a (meth)acrylic acid ester and a compound containing two or more vinyl groups in one molecule, and contains at least one -COONa group.

8. The absorbent article according to any one of claims 1 to 7, An absorbent article comprising an SAP capable of being adjacent to the polymer absorbent.

9. The absorbent article according to any one of claims 1 to 8, An absorbent article, characterized in that the void volume of said interconnected pores per unit volume of said polymer absorbent is 85% or more.

10. The absorbent article according to any one of claims 1 to 8, The absorbent article is characterized in that the polymer absorbent contains 0.1 to 30.0% of crosslinked polymer residues.

11. The absorbent article according to any one of claims 1 to 8, An absorbent article characterized in that the average diameter of the interconnected pores is 1 to 1000 μm.

Citation Information

Patent Citations

  • super absorbent polymer foam

    JP1996508527A

  • Absorptive article

    JP1998118117A

  • Hydrophilic polymer and method for producing the same

    JP2002507975A

  • JPP3699225B

  • Water absorbing resin particles, method for manufacturing water absorbing resin particles, absorption body, absorptive article, and water-sealing material

    WO2013018571A1